Proposal of a disruptive didactic innovation for the development of leadership skills through the arts: Skills & Art - Berlanga Fernández, Inmaculada; Pérez, Lucía; Palella, Santa; Cardona, Pablo (My University, 2024)
The need for cognitive and leadership skills requires the exploration of creative implementation models that ensure training and emphasise the value of individuals as the main asset within organisations. This research aims to introduce and validate a disruptive didactic innovation, which fosters the development of these skills through experiential communication via “Skills&Art”. The methodology used is Design Research, an emerging approach in educational research that encompasses developing and implementing a new or improved model, validating techniques, tools or models and determining conditions that facilitate successful implementation. The research was conducted in both classroom and museum settings. It consisted of a four-phase activity focused on crafting a speech that linked a skill with an artwork. A qualitative study of the speeches and a Likert self-assessment questionnaire were performed. The results demonstrate that the proposed disruptive didactic innovation Skills&Art is effective and efficient, and its self-assessed learning promotes innovation, creativity, initiative, problem solving and analytical thinking. The novelty and contribution of this study lie in implementing these thinking skills within a single activity
Keywords: innovation; learning; teaching experiment; soft skills; art; communication